Colchicine-Induced Genetic Variability in Porang (Amorphophallus muelleri): a Study Using SRAP Markers - Wahyudi, Didik; Suyono; Resmisari, Ruri Siti; Mauludyah, Rohmatul (Biotropika: Journal of Tropical Biology, 2025)
Mutation induction of porang both physically and chemically is widely used to increase the genetic variation of porang. However, mutation induction chemically by using colchicine is more effective than the other mutagens. Therefore, this study aims to assess the genetic diversity of porang after mutation induction using colchicine. Polyploidy induction is performed 30 days after planting of the porang plantlet. 0%, 0.01%, 0.02%, 0.03% and 0.04% colchicine was added to 12.5 ml of MS medium using a 0.22 µm Millipore filter. After 53 days, porang plantlets were ready for DNA isolation. A total of 10 SRAP primer combinations were used for DNA amplification. Genetic diversity in and between porang population was performed using POPGENE software. Clustering analysis using PAST Software was also performed to identify genetic variation. Mutation induction using colchicine significantly increased the genetic diversity of porang. Among the SRAP primer combinations, ME2-EM2 is the most effective in detecting the induced genetic variation in porang. Mutation induction using 0.03% colchicine is highly recommended as it produces significant genetic changes compared to normal porang. Porang mutant resulting from 0.03% colchicine treatment holds great potential for porang breeding programs, as it can generate novel phenotypic variations and increase the chances of obtaining superior genotypes with desirable agronomic traits.